Impact of Geographical Indications on Consumers’ Online Purchase of Fresh Agricultural Products - Zhan, Xinyi; Zhang , Yiming; Bai, Jiaming (Transactions on Economics, Business and Management Research, 2024)
Based on 257 consumer survey data, a binary logistic regression model is built to empirically test the relationship between multi-dimensional geographical indication characteristics, consumer perceived value and online purchase intention for fresh agricultural products with geographical indications. The results show that quality is the key dimension in the evaluation of geographical indications. Meanwhile, the market recognition, popularity, reputation and cultural history of geographical indications can significantly stimulate consumers’ online purchase intention, with the impacts of different dimensions varying. In addition, the popularity, reputation, product quality and cultural history of geographical indications can affect consumers’ perceived value, thereby affecting their purchase intention.